Isotopic landscapes in bioarchaeology : proceedings of the International Workshop "A Critical Look at the Concept of Isotopic Landscapes and its Application in Future Bioarchaeological Research", Munich, October 13-15, 2014 /: proceedings of the International Workshop "A Critical Look at the Concept of Isotopic Landscapes and its Application in Future Bioarchaeological Research", Munich, October 13-15, 2014. ([2016]) - Unknown
No abstract available